Adoption of interorganizational system standards in supply chains - An empirical analysis of RosettaNet standards - Alain Chong Yee, Loong; Ool, Keng-Boon (EMERALD GROUP PUBLISHING LIMITED, 2008)
Purpose - This study aims to empirically examine the factors that affect the adoption of RosettaNet standards. The four factors examined in this study are partners' power, trust, products' characteristics, and government influence.